THE RIGHT TO SPEAK OR SPEAK IT RIGHT: TEACHING ENGLISH SPEAKING IN INDONESIAN EFL CONTEXT - Asanti, Chris; Sudirman, Eka Pratiwi (CaLLs (Journal of Culture, Arts, Literature, and Linguistics), 2020)
ABSTRACTIn this contemporary world, along with the status of English as an international language to communicate, the teaching of English speaking has become increasingly significant in both ESL (English as a Second Language) and EFL contexts. This paper aims at highlighting and outlining the recent development of teaching speaking of English in Indonesian EFL context, especially in senior high schools. There are three major points discussed in this paper, first it discusses the current status of teaching speaking in Indonesia; second, it depicts the constraints that hinder in teaching English speaking in Indonesia related to native speaker model; and third it provides an explanation about teaching speaking for intercultural communication in Indonesia.Keywords: Teaching speaking, Native and Non-native speaker, Indonesian EFL context